Enigmatic carbon isotopic variability in the oceanic upper mantle - Yves Moussallam; Estelle F. Rose-Koga; Cyril Aubaud; Guillaume Georgeais; Pierre Cartigny; Kenneth T. Koga; Jean-Luc Devidal; Peter J. Michael; Kei Shimizu; Alberto E. Saal (Proceedings of the National Academy of Sciences, 2025)
Unraveling the origin(s) of carbon on Earth has remained challenging, not only because of the multiple isotopic fractionation episodes that may have occurred during planet formation processes but also because the end point of these processes, the current isotopic value of Earth’s deep carbon reservoirs remains poorly constrained. Here, we present carbon isotopic measurements on rare undegassed mid-ocean ridge basalts from the Pacific, Atlantic, and Arctic Oceans that have preserved the isotopic signature of their mantle source. We find that Earth’s present-day convecting upper mantle has variable δ 13 C value from ~−10 to −4‰, significantly different from the δ 13 C value of peridotitic diamonds and with the highest values being restricted to the Atlantic. Evidence for significant mantle heterogeneity contrasts with previous assumptions and its origin remains puzzling being uncorrelated with geochemical markers associated with either subduction and surficial recycling processes or lower mantle contributions. The data do not preclude other causes such as primordial mantle heterogeneity. We suggest that the δ 13 C value of the bulk silicate Earth may need to be revised.